Geomagnetic response to solar wind dynamic pressure impulse events at high‐latitude conjugate points. Issue 10 (1st October 2013) - Kim, H.; Cai, X.; Clauer, C. R.; R. Kunduri, B. S.; Matzka, J.; Stolle, C.; Weimer, D. R.
<x xml:space="preserve">Abstract</x> [1] It is commonly assumed that geomagnetic activity is symmetrical between interhemispheric conjugate locations. However, in many cases, such an assumption proved to be wrong. Especially in high‐latitude regions where the magnetosphere and the ionosphere are coupled in a more complex and dynamic fashion, asymmetrical features in geomagnetic phenomena are often observed. This paper presents investigations of geomagnetic responses to sudden change in solar wind pressure to examine interhemispheric conjugate behavior of magnetic field variations, which have rarely been made mainly due to the difficulty of facilitating conjugate‐point measurements. In this study, using magnetometer data from three conjugate stations in Greenland and Antarctica, solar wind pressure impulse events (>5 nPa in <16 min) and their geomagnetic responses, typically seen as magnetic impulse events, have been examined. Our results suggest that asymmetry in ground response patterns between the conjugate locations often shows little correlation with interplanetary magnetic field orientation, season, and ionospheric conductivity, indicating that much more complex mechanism might be involved in creating interhemispheric conjugate behavior.